Effect of gap voltage and pulse-on time on material removal rate for electrical discharge machining of Al2O3 - Moudood, M. A.; Sabur, Abdus; Ali, Mohammad Yeakub; Jaafar, Israd Hakim (Trans Tech Publications Ltd., Switzerland, 2015)
Electrical discharge machining (EDM) is a non-conventional machining technique which can be used to machine non-conductive ceramics. This technique removes materials from the workpiece by thermal energy exerted from series of electrical sparks. Using copper foil as assisting electrode (AE), machining of Al2O3 is done successfully. In this investigation, experiments were performed to study the effect of gap voltage and pulse-on time on material removal rate (MRR) for EDM of Al2O3. The results showed that the lowest and the highest values of gap voltage were 12 V and 14 V, respectively, with a fixed peak current of 1.1 A and pulse-on time of 8 μs. Beyond these two voltage values, material cannot be removed due to insufficient pyrolytic carbon layer generation. Similarly, pulse-on time is varied from 6 μs to 8 μs when gap voltage is fixed at 14 V and peak current at 1.1 A. MRR, in this case, is increased almost 20 times from a lowest value of 0.006 mm3/min to a highest value of 0.119 mm3/min for the specified gap voltage and pulse-on time.